A community survey of Cabanatuan City its implications for a program of informational services at the Nueva Ecija School of Arts and Trades - Diaz, Aurea Tayao 1921- (s.n.], 1963)
This community survey of Cabanatuan City provides necessary information needed by guidance counselors of the Nueva Ecija School of Arts and Trades so that these counselors may be sufficiently equipped to orient the students on the possibility of success in their chosen careers or occupations.